Characterizing the output settings of dental curing lights. (January 2016) - Harlow, J.E.; Sullivan, B.; Shortall, A.C.; Labrie, D.; Price, R.B.
Abstract: Objectives: For improved inter-study reproducibility and ultimately improved patient care, researchers and dentists need to know what electromagnetic radiation (light) is emitted from the light-curing unit (LCU) they are using and what is received by the resin. This information cannot be obtained from a dental radiometer, even though many studies have used a dental radiometer. Methods: The light outputs from six LCUs (two QTH and four broad-spectrum LED units) were collected in real-time using an integrating sphere connected to a fiberoptic spectrometer during different light exposures. Results: It was found that the spectral emissions were unique to each LCU, and there was no standardization in what was emitted on the various ramp (soft-start) settings. Relative to the normal use setting, using the ramp setting reduced the radiant energy (J) delivered from each LCU. For one of the four broad-spectrum LED LCUs, the spectral emissions in the violet range did not increase when the overall radiant power output was increased. In addition, this broad-spectrum LED LCU emitted no light from the violet LED chip for the first 5 s and only emitted violet light when the ramp phase finished. Conclusions: A single irradiance value derived from a dental radiometer or from a laboratory grade power meter cannot adequately describe the output from the LCU. Manufacturers should provide more information about the light output from their LCUs. Ideally, future assessments and research publications that include resin photopolymerization should report the spectral radiant power delivered from the LCU throughout the entire exposure cycle.